Web-Based Health Information Following the Renewal of the Cervical Screening Program in Australia: Evaluation of Readability, Understandability, and Credibility - Mac, Olivia A; Thayre, Amy; Tan, Shumei; Dodd, Rachael H (JMIR Publications, 2020)
BackgroundThree main changes were implemented in the Australian National Cervical Screening Program (NCSP) in December 2017: an increase in the recommended age to start screening, extended screening intervals, and change from the Papanicolaou (Pap) test to primary human papillomavirus screening (cervical screening test). The internet is a readily accessible source of information to explain the reasons for these changes to the public. It is important that web-based health information about changes to national screening programs is accessible and understandable for the general population. ObjectiveThis study aimed to evaluate Australian web-based resources that provide information about the changes to the cervical screening program. MethodsThe term cervical screening was searched in 3 search engines. The first 10 relevant results across the first 3 pages of each search engine were selected. Overall, 2 authors independently evaluated each website for readability (Flesch Reading Ease [FRE], Flesch-Kincaid Grade Level, and Simple Measure of Gobbledygook [SMOG] index), quality of information (Patient Education Materials Assessment Tool [PEMAT] for printable materials), credibility (Journal of the American Medical Association [JAMA] benchmark criteria and presence of Health on the Net Foundation code of conduct [HONcode] certification), website design, and usability with 5 simulation questions to assess the relevance of information. A descriptive analysis was conducted for the readability measures, PEMAT, and the JAMA benchmark criteria. ResultsOf the 49 websites identified in the search, 15 were eligible for inclusion. The consumer-focused websites were classed as fairly difficult to read (mean FRE score 51.8, SD 13.3). The highest FRE score (easiest to read) was 70.4 (Cancer Council Australia Cervical Screening Consumer Site), and the lowest FRE score (most difficult to read) was 33.0 (NCSP Clinical Guidelines). A total of 9 consumer-focused websites and 4 health care provider-focused websites met the recommended threshold (sixth to eighth grade; SMOG index) for readability. The mean PEMAT understandability scores were 87.7% (SD 6.0%) for consumer-focused websites and 64.9% (SD 13.8%) for health care provider-focused websites. The mean actionability scores were 58.1% (SD 19.1%) for consumer-focused websites and 36.7% (SD 11.0%) for health care provider-focused websites. Moreover, 9 consumer-focused and 3 health care provider-focused websites scored above 70% for understandability, and 2 consumer-focused websites had an actionability score above 70%. A total of 3 websites met all 4 of the JAMA benchmark criteria, and 2 websites displayed the HONcode. ConclusionsIt is important for women to have access to information that is at an appropriate reading level to better understand the implications of the changes to the cervical screening program. These findings can help health care providers direct their patients toward websites that provide information on cervical screening that is written at accessible reading levels and has high understandability.